Analysis of Enterprise Resource Planning Integration in Supply Chain Management at PT. Dayamitra Telekomunikasi (Mitratel) - Noval Murizadin, Noval Murizadin; Mulyani Sari, Rini (International Journal of Science, Technology & Management, 2025)
This study aims to understand and analyze the integration of Enterprise Resource Planning (ERP) systems in Supply Chain Management (SCM) at PT Dayamitra Telekomunikasi. The method used in this research is qualitative research. Data collection techniques were conducted through interviews with managers and officers from Mitratel. The results of the study indicate that the integration of ERP in SCM at Mitratel has a positive impact on the efficiency and effectiveness of SCM operations, allowing the company to gain a competitive advantage. Research on ERP integration in SCM at PT Dayamitra Telekomunikasi is still limited. Therefore, it is recommended to conduct further in-depth research on ERP integration in SCM at Mitratel.